In vivo Genotoxicity of Silver Nanoparticles after 90-day Silver Nanoparticle Inhalation Exposure - Jin Sik Kim; Jae Hyuck Sung; Jun Ho Ji; Kyung Seuk Song; Ji Hyun Lee; Chang Soo Kang; Il Je Yu (Elsevier, 2011)
Objectives: The antimicrobial activity of silver nanoparticles has resulted in their widespread use in many consumer products. Yet, despite their many advantages, it is also important to determine whether silver nanoparticles may represent a hazard to the environment and human health. Methods: Thus, to evaluate the genotoxic potential of silver nanoparticles, in vivo genotoxicity testing (OECD 474, in vivo micronuclei test) was conducted after exposing male and female Sprague-Dawley rats to silver nanoparticles by inhalation for 90 days according to OECD test guideline 413 (Subchronic Inhalation Toxicity: 90 Day Study) with a good laboratory practice system. The rats were exposed to silver nanoparticles (18 nm diameter) at concentrations of 0.7 × 106 particles/cm3 (low dose), 1.4 × 106 particles/cm3 (middle dose), and 2.9 × 106 particles/cm3 (high dose) for 6 hr/day in an inhalation chamber for 90 days. The rats were killed 24 hr after the last administration, then the femurs were removed and the bone marrow collected and evaluated for micronucleus induction. Results: There were no statistically significant differences in the micronucleated polychromatic erythrocytes or in the ratio of polychromatic erythrocytes among the total erythrocytes after silver nanoparticle exposure when compared with the control. Conclusion: The present results suggest that exposure to silver nanoparticles by inhalation for 90 days does not induce genetic toxicity in male and female rat bone marrow in vivo.